Cardiovascular health and retinal microvascular geometry in Australian 11-12 year-olds - Mengjiao Liu; Kate Lycett; Melissa Wake; Mingguang He; Jessica A. Kerr; Richard Saffery; Markus Juonala; Tim Olds; Terry Dwyer; David P. Burgner; Tien Yin Wong (Academic Press., 2022)
Traditional retinal microvascular parameters (smaller arteriolar and greater venular caliber) are associated with cardiovascular risk factors, pre-clinical vascular phenotypes and clinical cardiovascular events in adults. Although novel retinal microvascular geometric parameters showed analogous associations in adults, less is known whether these parameters are associated with cardiovascular health from childhood. In a population-based cross-sectional study in children (n = 1126, mean age 11.4 years, 50.3% girls), we examined associations of cardiovascular risk factors and pre-clinical arterial phenotypes with retinal geometric parameters. Cardiovascular parameters included body mass index (BMI), an inflammatory marker (GlycA), low-density lipoprotein and high-density lipoprotein (HDL) cholesterol, systolic (SBP) and diastolic blood pressure, large artery functional (pulse wave velocity, PWV and carotid arterial elasticity) and structural (carotid intima-media thickness) phenotypes. Retinal geometric parameters (fractal dimension (Df) and tortuosity) were quantified from retinal images. Multivariable regression models were performed and adjusted for potential confounders. Higher values for BMI, SBP and PWV showed weak associations with lower (i.e. worse) arteriolar but not venular Df (standardized mean difference (SMD) ranging from −0.07 to −0.09, 95% CIs −0.15 to −0.01). Higher HDL was associated with greater arteriolar Df (SMD 0.07, 95% CI 0.01 to 0.13). Only higher SBP was associated with higher (i.e. worse) arteriolar but not venular tortuosity (SMD 0.09, 95% CI 0.02 to 0.16). In generally healthy children, some risk factors and pre-clinical arterial phenotypes show small associations with retinal geometric parameters. In childhood, emerging relationships between microvascular parameters and cardiometabolic risk may be better described by retinal vascular caliber than by geometric parameters.